THE AFFECTS OF GROSS REGIONAL DOMESTIC PRODUCT (GRDP) AND THE MINIMUM WAGE ON EMPLOYMENT IN WEST JAVA PROVINCE - Rozi, Khansa Nabila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This writing paper possess objective to observe and analyze the impact of the independent variables towards the employment variable or it is well known as the dependent variable. The independent variables applied within this research analysis were Gross Regional Domestic Product and minimum wage. This research study analysis utilized a secondary annual time series data from 2010 until 2014. The method that is applied in this research was panel data regression with the approach of Fixed Effect Model. According to this study, the result revealed that the minimum wage is give a significant and positive influence to employment, and also Gross Regional Domestic Product is give a significant and positive influence to employment.Â Keywords: GRDP, Minimum Wage, Employment.